A critical review on marine litter in the Adriatic Sea: Focus on plastic pollution. (15th March 2021) - Schmid, Chiara; Cozzarini, Luca; Zambello, Elena
Abstract: Marine litter affects various habitats across the world. This review focuses on the Adriatic region, considering the presence of marine litter as well as microplastics (mPs) and macroplastics (MPs) in different environments (water, beach, seabed and biota). Data from 53 scientific papers were critically analysed, providing a snapshot of this type of contamination, and evidencing critical issues. The final part of the review provides considerations on spatial and temporal trends, comparing data with the available information provided by transport forecasting models. It emerges that the most investigated areas are those most subjected to the contribution of rivers, tourism or have the greatest relevance to nature conservation. Our analysis also reveals that, even though many international research projects have played a fundamental role in the creation of shared methods and protocols, currently available data are difficult to compare. Nevertheless, our results enhance knowledge of the state of the art in the research carried out so far, and on the situation regarding pollution due to the marine litter in the Adriatic Sea, as well as highlighting avenues for future investigation. Graphical abstract: Image 1 Highlights: The studies on the presence of marine litter in the Adriatic region are collected. Plastic has been found in sea water, sea bed, beaches and biota. Polyolefin is the main type of plastic found in the investigated environments. Comparison and monitoring data is difficult when uniform protocols are not adopted. The available protocols should be improved to obtain more representative data. Abstract : All the main studies on the presence of marine litter in the Adriatic region are analysed, finding that different protocols were used, and highlighting the different types of plastic present in seawater, sea bed, beaches and biota.